2021
DOI: 10.3389/fmed.2021.739251
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Intervention of Sex Steroid Hormones for Sarcopenia

Abstract: Sarcopenia, characterized by the excessive loss of skeletal muscle mass, strength, and function, is associated with the overall poor muscle performance status of the elderly, and occurs more frequently in those with chronic diseases. The causes of sarcopenia are multifactorial due to the inherent relationship between muscles and molecular mechanisms, such as mitochondrial function, inflammatory pathways, and circulating hormones. Age-related changes in sex steroid hormone concentrations, including testosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 145 publications
(179 reference statements)
0
15
0
1
Order By: Relevance
“…Many studies have proved that sarcopenia was related to mitochondrial function, and improving mitochondrial dysfunction was an important target for the treatment of sarcopenia. 19,37,38 Whether the improvement of C. elegans sarcopenia by linolenic acid is related to mitochondrial function was determined. Two transgenic C. elegans strains CB5600 and SJ4103 were used to investigate the effects of linolenic acid administration on myotome morphology.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have proved that sarcopenia was related to mitochondrial function, and improving mitochondrial dysfunction was an important target for the treatment of sarcopenia. 19,37,38 Whether the improvement of C. elegans sarcopenia by linolenic acid is related to mitochondrial function was determined. Two transgenic C. elegans strains CB5600 and SJ4103 were used to investigate the effects of linolenic acid administration on myotome morphology.…”
Section: Resultsmentioning
confidence: 99%
“…However, both replacement therapies have been shown to be associated with severe side effects [ 5 , 7 ]. Consequently, due to higher tissue selectivity, selective androgen and estrogen receptor modulators (SARM and SERM, respectively) offer new treatment options for the musculoskeletal system [ 2 ]. SARMs resist aromatization of 5-α-reduction compared to testosterone and are considered to have a better bioavailability and pharmacokinetic profile than testosterone [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there has been no indication for their use so far [ 9 ]. SERMs present an established therapy for postmenopausal symptoms that have fewer side effects compared to estrogen [ 2 ]. In regard to musculature, studies reported improved muscle function and structure after SERM administration in male mice with muscular dystrophy [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, sarcopenia has been recognized as a disease since its registration in the International Classification of Disease, Tenth Revision, Clinical Modification on October 1, 2016 ( 8 , 9 ). In recent years, several pharmacological treatments, including synthetic drugs and hormones, have been tested for the improvement of sarcopenia in clinical trials ( 10 12 ). However, it has been reported that testosterone may increase the risk for cardiovascular adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that testosterone may increase the risk for cardiovascular adverse events. Selective androgen receptor modulators have been used to avoid the side effects of anabolic steroids, but constipation, dyspepsia, or nausea have also been observed in studies ( 10 ). Growth hormone increased lean body mass and decreased fat mass; however, adverse events such as soft tissue edema, arthralgias, and carpal tunnel syndrome were significantly increased in the clinical trial ( 11 ).…”
Section: Introductionmentioning
confidence: 99%